Real time heart rate estimation from severely corrupted PPG signal by motion artifact - Imtiaz, Mohammad Masuk; Tina, Tahmina Ahmed (BRAC University, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.